Extreme weather and ratings on corporate climate mitigation policies. Issue 4 (27th July 2021) - Chen, Dong
Abstract: This study examines whether the extreme weather events (EWEs) incurred at the headquarters of firms have an impact on their climate mitigation policies. I show that, controlling for county fixed effects, the annual number of EWEs at the headquarter counties of the largest public firms in the US significantly improves the subsequent ratings of their climate mitigation policies, with recent EWEs having a more pronounced impact. I also find that the EWEs at the neighboring counties do not have a similar effect, and provide some evidence that the impact of EWEs on climate ratings is stronger for weakly governed firms, and that some EWEs positively affect the likelihood of utility firms' expressing a concern for climate risk through their SEC filings. These results support the idea that personal weather experiences can influence managerial belief in anthropogenic climate change which in turn affects corporate climate mitigation policies.